Electrospun nylon-6 nanofibers and their characteristics - Sriyanti, Ida; Agustini, Meily P; Jauhari, Jaidan; Sukemi, Sukemi; Nawawi, Zainuddin (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
The purposes of this research were to investigate the synthesized Nylon-6 nanofibers using electrospinning technique and their characteristics. The method used in this study was an experimental method with a quantitative approach. Nylon-6 nanofibers have been produced using the electrospinning method. This fiber was made with different concentrations, i.e. 20% w/w (FN1), 25% w/w (FN2), and 30% w/w (FN3). The SEM results show that the morphology of all nylon-6 nanofibers) forms perfect fibers without bead fiber. Increasing fiber concentration from 20% w/w to 30% w/w results in bigger morphology and fiber diameter. The dimensions of the FN1, FN2, and FN3 fibers are 1890 nm, 2350 nm, and 2420 nm, respectively. The results of FTIR analysis showed that the increase in the concentration of nylon-6 (b) and the electrospinning process caused a peak shift in the amide II group (CH2 bond), the carbonyl group and the CH2 stretching of the amide III group from small wave numbers to larger ones. The results of XRD characterization showed that the electrospinning process affected the changes in the XRD pattern of nylon-6 nanofiber (FN1, FN2, and FN3) in the state of semi crystal. Nylon-6 nanofibers can be used for applications in medicine, air filters, and electrode for capacitors